(untitled) (Portuguese Journal of Family Medicine and General Practice, 2004)
The study wanted to show the prevalence of obesity and weight in excess in a surveillance clinic of children aged between 11 and 13 years at the Santarém Health Center. We wanted to determine body mass index, daily number of meals, practice of sport activities outside school, hobbies and laboratory changes related to excess weight in the children who participated in the study. It was a descriptive observational study, which had initially 231 children aged between 11-13 years that were asked to come to a surveillance visit in the Health Center of Santarém; 135 (58.4%) attended. We noted that 5.2% of the children were obese; 21.5% had weight in excess; 77.6% of the observed children had five or more meals during the day; 50.4% of them do sport outside the school; 51.9% have hobbies of non-sedentary activities; and only 3% showed changes in their lipidic status. The results of the weight in excess and obesity showed the need to define preferential groups to define interventions of promotion of the food habits and physical exercise in these children.